2019
DOI: 10.1111/ppl.13022
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics and metabolomics reveal the tolerance mechanism to low nitrogen in Glycine soja leaves

Abstract: To explore the regulatory mechanisms involved in the adaption to nitrogen (N) deficiency of wild soybean, the ion balance, photosynthetic characteristics, metabolic and transcriptional changes in leaves of common and low N (LN)-tolerant wild soybean seedlings under LN stress were determined. The LN-tolerant wild soybean seedlings showed a stronger ability to maintain photosynthesis and nutrient balance than common wild soybean. A total of 52 differentially accumulated metabolites, mainly related to carbon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The saturated and monounsaturated fatty acids accumulated when the N concentration was decreased [ 45 ]. It has been reported that N-deficient-tolerant soybean maintained higher chlorophyll content, as well as increased fatty acid metabolism [ 46 ]. Recently, in cultivated wheat, there were close relationships between the alteration in membrane lipid and fatty acid compositions and the plant N-deficiency response under N deficiency condition [ 31 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The saturated and monounsaturated fatty acids accumulated when the N concentration was decreased [ 45 ]. It has been reported that N-deficient-tolerant soybean maintained higher chlorophyll content, as well as increased fatty acid metabolism [ 46 ]. Recently, in cultivated wheat, there were close relationships between the alteration in membrane lipid and fatty acid compositions and the plant N-deficiency response under N deficiency condition [ 31 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The energy was -70 eV in electron impact mode. The mass spectrometry data were acquired in full-scan mode with the m/z range of 50-500 at a rate of 12.5 spectra per s after a solvent delay of 6.30 min (Zhao et al 2019).…”
Section: Gc-tof-ms Analysismentioning
confidence: 99%
“…Wild soybean (Glycine soja ) is the related species of cultivated soybean, which has a higher resistance to disease, insect, drought, and nutrient deficiency than cultivated soybean. Our previous results found that wild soybean can tolerate low nitrogen and drought stresses by maintaining nutrient balance and stable tricarboxylic acid (TCA) cycle and increasing the concentration of metabolites such as amino acids (Wanget al 2019;Zhao et al 2019). Nevertheless, the adaptation mechanism of wild soybean and cultivated soybean under low P conditions is still not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the TCA cycle, shikimic acid pathway, synthetase/glutamate synthase (GS/GOGAT) cycle, and accumulation of most organic acids were enhanced in the low N-tolerant genotype of wild soybean (Glycine soja Sieb.) but reduced in the common genotype (Zhao et al, 2020). In wild barley (Hordeum spontaneum L.), low N affected the glycolysis, TCA, and pentose phosphate pathways, while the tolerant genotype accumulated energysaving amino acids, distributed carbon to roots, and had a higher capacity to maintain redox homeostasis (Quan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%